Analisis Kontekstual pada Strategi Keamanan Siber Mesir 2017-2021 dalam Upaya Pengamanan Siber Nasional - Dian Islami (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2021)
This study aims to understand and analyze Egypt's cybersecurity strategy in 2017-2021 related to the level of security and the role of each aspect of the cybersecurity strategy in the Egyptian state. This research was conducted because Egypt and Indonesia have several similarities, such as countries with a Muslim majority and fellow members in the Islamic Cooperation Organization, the Non-Aligned Movement, the G-20 developing countries, and the group of 8 developing countries. Qualitative methods are used to analyze the application of the concept of sovereignty theory which is exclusive or transfer, as well as aspects of cybersecurity which include infrastructure, application, and core (ideology). Meanwhile, quantitative methods are used to present the results of data analysis on Egyptian cybersecurity data relations and strategies with MAXQDA2020 and Gephi 0.9.2 applications. Based on the results of the analysis, the authors conclude that the context of Egypt's cybersecurity strategy has a tendency towards collaboration between state actors and non-state-actors based on aspects of national cybersecurity, cybersecurity awareness, cyberspace threats, international rules, laws and regulations, cyber crisis nation-wide. , cybercrime, and cyberinfrastructure. This aspect can be used in the formulation of Indonesia's national cybersecurity strategy policy in the coming year.